David Gordon White, The Yoga Sutra of Patanjali. A Biography, Princeton, Princeton University Press, 2014, 273 pp. - Muñoz, Adrián (El Colegio de México, 2015)
David Gordon White, The Yoga Sutra of Patanjali. A Biography, Princeton, Princeton University Press, 2014, 273 pp.